Branding para las artesanías elaboradas con totora, de la parroquia Chantilín, cantón Saquisilí, provincia de Cotopaxi - Changoluisa Semblantes, Flavio Samuel (2017)
To be Branding a cumulus of strategies which help to the management of brand of the organizations and point of difference of products, it has been considered to a group of artisans in Saquisilí canton belonging to the Cotopaxi province, dedicated in the most part to the agricultural and livestock activities where the 5% of its population sits in rural sectors, among them is located San Francisco neighborhood in Chantilin parish, where rises an initiative of entrepreneurship between their residents, to generate economic income through the elaboration of handicrafts, in order to take advantage of an unusual plant called totora which grows in humid places in the sector, which with the correct process becomes in raw material to elaborate craft articles. The objective of this project is to develop a strategy of SocialBrain which implies the audiovisual production, of the craft elaborated with totora (herbaceous aquatic plant, common in marshes and swamps, abundant in Ecuador) in San Francisco neighborhood belonging to the Chantilin parish in Saquisili canton, the project starts with the compilation of bibliographic information, the same which determined the epistemological bases of the Branding based in the criterion of Joan Costa (2015), who recognize to the Branding as the fundamental basis of the visual communication, Also a qualitative methodology was applied which permit us to collect information of the activity which is made for the independent craftsmen....